1967
DOI: 10.1038/bjc.1967.55
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma in infancy and childhood in Ibadan, Western Nigeria.

Abstract: ALTHOUGH primary malignant tumours of the liver occur rarely in early life, there are quite a number of cases in the literature from different parts of the world. These cases have been reviewed from time to time and additional cases have been recorded (Steiner, 1938;Drummond and Tollman, 1939;Edmondson, 1956;Clatworthy and Boles, 1961;Kasai, 1963; Fish, McCarey and Galveston, 1966;Misugi et al., 1966). Reviewing the literature, there are no reports of these tumours in several parts of Africa, particularly in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1969
1969
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 6 publications
(4 reference statements)
0
10
0
Order By: Relevance
“…However, tumors induced by PAs also were found in lung, kidney, skin, bladder, brain and spinal cord, pancreatic islets and adrenal gland (Allen et al, 1975;Brandange et al, 1970;Chan et al, 1994;Cook et al, 1950;Furuya et al, 1976;Harris and Chen, 1970;Hirono et al, 1976Hirono et al, , 1977Hirono et al, , 1978Hirono et al, , 1979Hirono et al, , 1983Johnson et al, 1978;Kuhara et al, 1980;Mattocks and Cabral, 1982;Mori et al, 1984;Peterson et al, 1983;Rao et al, 1983;Rao and Reddy, 1978;Schoental, 1975;Schoental and Cavanagh, 1972;Schoental et al, 1954Schoental et al, , 1970Schoental et al, , 1971Schoental and Head, 1957;Shumaker et al, 1976;Reddy, 1972, 1974;Williams, 1970). Despite no clear evidence that PAs induce tumors in humans, the frequent occurrence of primary liver tumors in the natives of Central Africa and South Africa has been associated with the consumption of traditional medicinal PA-containing plants (Pavlica and Samuel, 1970;Schoental, 1968;Schoental and Coady, 1968;Williams et al, 1967). It has been reported that PA-containing plants induce hepatic veno-occlusive disease in humans.…”
Section: Carcinogenicity and Hepatotoxicitymentioning
confidence: 99%
“…However, tumors induced by PAs also were found in lung, kidney, skin, bladder, brain and spinal cord, pancreatic islets and adrenal gland (Allen et al, 1975;Brandange et al, 1970;Chan et al, 1994;Cook et al, 1950;Furuya et al, 1976;Harris and Chen, 1970;Hirono et al, 1976Hirono et al, , 1977Hirono et al, , 1978Hirono et al, , 1979Hirono et al, , 1983Johnson et al, 1978;Kuhara et al, 1980;Mattocks and Cabral, 1982;Mori et al, 1984;Peterson et al, 1983;Rao et al, 1983;Rao and Reddy, 1978;Schoental, 1975;Schoental and Cavanagh, 1972;Schoental et al, 1954Schoental et al, , 1970Schoental et al, , 1971Schoental and Head, 1957;Shumaker et al, 1976;Reddy, 1972, 1974;Williams, 1970). Despite no clear evidence that PAs induce tumors in humans, the frequent occurrence of primary liver tumors in the natives of Central Africa and South Africa has been associated with the consumption of traditional medicinal PA-containing plants (Pavlica and Samuel, 1970;Schoental, 1968;Schoental and Coady, 1968;Williams et al, 1967). It has been reported that PA-containing plants induce hepatic veno-occlusive disease in humans.…”
Section: Carcinogenicity and Hepatotoxicitymentioning
confidence: 99%
“…Kaposi's sarcoma has already been described elsewhere;16.27.28 and rhabdomyosarcoma of the upper respiratory tract and face have also been described elsewhere. 36 When it affects the face, the differential diagnosis is Burkitt's lymphoma. 44 Botryoid sarcoma of the ear, nasopharynx, uvula, bladder, and uterus was also encountered infrequently.…”
Section: Soft Tissue Tumorsmentioning
confidence: 99%
“…Based on the similar mode of mutagenic and tumorigenic actions of PAs in different experimental models, the mutagenicity of PAs and associated carcinogenic risks in humans should be seriously considered. Notably, despite no clear evidence supporting PA-induced tumors in humans, the frequent occurrence of primary liver tumors in the natives of Central Africa and South Africa has been reported to be associated with the consumption of PA-containing traditional medicinal plants (Pavlica and Samuel 1970;Schoental 1968;Williams et al 1967). However, the lack of specific and definitive biomarkers for diagnosis of PA-induced genotoxicity hampers the evaluation of such health risks in clinical practice.…”
Section: Pdas As a Biomarker Of Pa-induced Genotoxicity And Tumorigenicitymentioning
confidence: 99%